The relationship of acculturative stress with meaning in life through the mediating role of difficulties in emotion regulation and meaning-centered coping style among international students in Germany - Soufi Amlashi, Rasa; Forstmeier, Simon (Frontiers in Psychology, 2025)
IntroductionWith the increasing trend of international academic mobility, understanding the psychological outcomes of cultural transition has become crucial. The present study aimed to examine the relationship between acculturative stress and meaning in life (MIL), focusing on the mediating roles of difficulties in emotion regulation (DIER) and meaning-centered coping style (MCCS) among international students in Germany.MethodsThis descriptive-correlational study recruited 443 students enrolled at German universities in 2024 through convenience sampling. Participants completed Sandhu & Asrabadi’s Acculturative Stress Scale for International Students, Gratz & Roemer’s DIER Scale, Eisenbeck et al.’s Meaning-Centered Coping Scale, and Steger et al.’s Meaning in Life Questionnaire. Data were analyzed using Pearson’s correlation coefficient and structural equation modeling (SEM) in SPSS-26 and LISREL-10.20.ResultsThe findings indicated that acculturative stress was directly and positively associated with the search for meaning, and indirectly associated with both the presence of meaning and the search for meaning through DIER and MCCS. Specifically, acculturative stress was positively related to DIER, which in turn was negatively associated with the presence of meaning and positively with the search for meaning. Additionally, acculturative stress was negatively related to MCCS, which was positively linked to the presence of meaning, but not significantly to the search for meaning.DiscussionThese results underscore the significance of emotional regulation and MCCS in mitigating the psychological effects of acculturative stress and promoting psychological wellbeing among international students.